(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
Construction problems have always been an important part in learning Geometry. The following article is a new way to use technology to create geometric constructions instead of using an old-school ruler and compass. This will help teachers incorporate technology in the classroom and save time and materials in the process.